THE ROLE OF AI IN SERIOUS GAMES: LEARNING THROUGH PLAY IN EDUCATION AND TRAINING - Komilova Hilola (Web of Journals Publishing, 2025)
This study investigates the transformative potential of AI-powered serious games in education and training, focusing on their ability to enhance student engagement and knowledge retention. Serious games, designed for learning rather than entertainment, leverage AI to personalize content and adapt challenges. Using a mixed-methods approach, this research evaluates games like *Eco* (environmental management simulation) and *AI for Oceans* (machine learning training) in university settings. Findings reveal a 70% increase in student motivation and a 65% improvement in retention of complex concepts. The study highlights AI’s role in creating interactive learning environments and recommends integrating these games into curricula to foster critical thinking and practical skills. It also identifies challenges, such as the need for teacher training, and suggests future research directions for broader adoption
Keywords: AI, serious games, education, training, engagement, gamification, learning outcomes.